Exploring the Concept of Children as a Fitnah in Islamic Family Law: A Deeper Understanding - Luthfi, Moh.; Musdatulia, Musarika; Fauzan, Ahmad; Baihaqi, Yusuf (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
In marriage, the presence of a child is one of the greatest blessings granted by Allah SWT to a husband and wife. The arrival of a child can be a source of joy and comfort for the parents, and the child can also be a adornment for both parents. However, it is important to recognize that a child can also become a fitnah for the parents, as mentioned in Q.S. at-Tagābun verse 15. When examining the verses concerning fitnah in the Qur'an, we find that there are many different meanings of fitnah, which may vary significantly when compared to its definition in the Indonesian Dictionary. This study aims to explore the understanding of the concept of